Pengaruh Kepemimipinan Terhadap Kinerja Pegawai Sekretariat Daerah Kabupaten Pasaman Barat - Nikmatul Husna (Riset Sinergi Indonesia, 2022)
Abstract. This research with the title The Influence Of Leadership Toward Employee Performance Distric Regional Secretariat Pasaman Barat. The purpose of this research is to identify and analyze the influence of leadership toward employee performance distric regional secretariat Pasaman Barat. The population of the research is the employee in distric regional secretariat Pasaman Barat. Samples taken are 99 respondents by using census technique. Based on hypothesis in this research, it is assumed that the influence of leadership significantly and positively influence employee performance Distric Regional Secretariat Pasaman Barat. The data analysis methods author used in this research are validity tes, reliability test, variable descriptive analysis test, simple linear regression analysis, T test and F test. From analysis that have been done, author found that leadership variable (X) is significantly and positively influence the employee performance, this is proven by the significant probability value of leadership is resulted in 0,000 which is smaller than 0,05. From F test, it can be concluded that regression model can be use to predict the leadership which have significantly and positively influence toward employee performance by the significant probability value is resulted in 0,000 which is smaller than 0,05.